IMPLEMENTATION OF LEGAL PRODUCT AGREEMENT PT. ALLIANZ LIFE INDONESIA INSURANCE (SMARTLINK FLEXI ACCOUNT PLUS) - Poetri Enindah Suradinata; Fitriani Fitriani; Zegovia Parera (Jurnal Restorative Justice, 2022)
Abstract The aims of this article is to analyze the law of the product agreement "SmartLink Flexi Account Plus" at PT. Allianz Life Indonesia Insurance. Where the product program provides life insurance protection for the insured by having two benefits at once, namely life insurance benefits and investment value. The research method used in this study is a normative juridical research method, carried out by examining primary data obtained/collected directly from related parties, namely the company and customers of PT. Allianz Life Indonesia Insurance Jayapura Branch. In this study, two approaches were used, namely the law approach and the case approach. The sources of legal materials in this study are primary legal materials, secondary legal materials and tertiary legal materials. Based on the research results obtained, the life insurance customers "Smartlink Flexi Account Plus" are guaranteed life insurance benefits up to the age of 100 years/for life, additional insurance benefits (riders) and the benefits of an all in onethe life insurance customers "Smartlink Flexi Account Plus" are guaranteed life insurance benefits up to the age of 100 years/for life, additional insurance benefits (riders) and the benefits of an all in one policy investment value. With the implementation of an agreement between the Insurer and the Insured, in which the insurance company or insurer is obliged to pay insurance compensation in the event of insurance risk to the insured and return the investment value formed, the Insured's obligation is to pay a premium. The form of the agreement is written in the insurance policy book.